Isolated Spontaneous Mesenteric Artery Dissection: A Rare Entity - Pradhan, Akshyaya; Bhandari, Monika; Vishwakarma, Pravesh; Kumar, Shailendra; Rai, Anurag (International Journal of Angiology, 2021)
Isolated spontaneous dissection of the mesenteric artery in the absence of involvement of the aorta or its branches is an uncommon vascular entity. It is generally seen in males and presents with gastrointestinal symptoms due to mesenteric ischemia. However, asymptomatic cases are increasingly being diagnosed due to increased use of computed tomography (CT) angiography. The course is usually self-limiting, and conservative management with bowel rest, strict blood pressure control, anticoagulants, sedatives for pain, and close observation usually suffices. Surgery or endovascular stenting is usually reserved for those exhibiting bowel ischemia or impending rupture. We report a case of a young female with isolated spontaneous mesenteric artery dissection with thrombus, which did not improve with medical therapy and was managed promptly by surgery due to the presence of bowel ischemia.
Keywords: superior mesenteric artery; CT angiography; mesenteric ischemia; thrombus; bypass surgery